Urethral atrophy is now a rare cause for artificial urinary sphincter revision surgery in the contemporary 3.5 cm cuff era - Bergeson, Rachel L.; Yi, Yooni A.; Baker, Ryan C.; Ward, Ellen E.; Davenport, Michael T.; Morey, Allen F. (Translational Andrology and Urology; Vol 9, No 1 (February 01, 2020): Translational Andrology and Urology (Current Topics of Reconstructive Urologic Surgery), 2019)
Background: Urethral atrophy has long been suggested as the leading cause of artificial urinary sphincter (AUS) revision. Since the introduction of the 3.5 cm AUS cuff in 2010, precise cuff sizing primarily has been suggested to reduce revisions due to urethral atrophy. We evaluated a large contemporary series of reoperative AUS cases to determine reasons for revision surgery. Methods: We retrospectively reviewed our tertiary referral center database of male AUS procedures performed by a single surgeon from 2007–2019. AUS revision or replacement procedures were included for analysis. Cuff sizes and reasons for reoperation were recorded based on intraoperative findings and evaluated for temporal trends. Patients with cuff erosion or lacking follow-up were excluded. Results: Among 714 AUS cases, 177 revisions or replacements were identified. Of these, 137 met inclusion criteria [mean age 71.7 years, median follow-up 52.7 months (IQR 22.3–94.6 months)]. Urethral atrophy was cited as the cause of AUS failure in 8.0% (11/137) of cases overall, virtually never among those with a 3.5 cm cuff placement (1/51, 2.0%). In those with ≥4.0 cm cuffs, urethral atrophy was the reason for revision in 10/86 (11.6%). Pressure regulating balloon (PRB) failure was the most frequently cited cause of failure (47/137, 34.3%). Cuff-related failure (23/137, 16.8%) and mechanical failure of unspecified device component (16/137, 11.8%) were the next most frequent causes of failure. Conclusions: Urethral atrophy has become a rare cause of AUS revision surgery since the availability of smaller cuffs. PRB-related failure is now the leading cause of AUS reoperation.